Sustainable green catalysis by supported metal nanoparticles - Fukuoka, Atsushi; Dhepe, Paresh Laxmikant (Chemical Record, 2009)
The recent progress of sustainable green catalysis by supported metal nanoparticles is described. The template synthesis of metal nanoparticles in ordered porous materials is studied for the rational design of heterogeneous catalysts capable of high activity and selectivity. The application of these materials in green catalytic processes results in a unique activity and selectivity arising from the concerted effect of metal nanoparticles and supports. The high catalytic performances of Pt nanoparticles in mesoporous silica is reported Supported metal catalysts have also been applied to biomass conversion by heterogeneous catalysis Additionally, the degradation of cellulose by supported metal catalysts, in which bifunctional catalysis of acid and metal plays the key role for the hydrolysis and reduction of cellulose, is also reported. (C) 2009 The Japan Chemical Journal Forum and Wiley Periodicals, Inc. Chem Rec 9: 224-235: 2009: Published online in Wiley InterScience (www.intersciencewiley.corn) DOI 10.1002/tcr.200900004
Keywords: Biomass; cellulose; CO oxidation; Mesoporous silica; supported metal catalyst

Solid-acid-based process for the conversion of hemicellulose - Dhepe, Paresh Laxmikant; Sahu, Ramakanta (Green Chemistry, 2010)
We describe a solid-acid-catalyzed conversion of hemicellulose (a component of lignocellulosic material) into xylose, arabinose and furfural in aqueous media.

Silica and zirconia supported tungsten, molybdenum and gallium oxide catalysts for the synthesis of furfural - Bhaumik, Prasenjit; Kane, Tanushree; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2014)
SiO2 and ZrO2 supported W, Mo and Ga oxide catalysts were prepared by a sol-gel and wet-impregnation method. The 10 wt% WO3/SiO2 (sol-gel) catalyst showed 61 +/- 2% furfural yield from hemicellulose in a one-pot fashion for at least 8 cycles. Based on XRD, TPD and Hammett acidity characterizations, the catalyst structure-activity correlation was drawn.

Solid acid catalyzed depolymerization of lignin into value added aromatic monomers - Deepa, Ayillath K.; Dhepe, Paresh Laxmikant (RSC Advances, 2014)
Depolymerization of lignin to produce value-added aromatic monomers has attracted a lot of attention since these monomers can potentially be used as fuel additives (octane enhancers) and in turn can improve the prospects of cellulosic ethanol technology to become economically feasible. Here we show that solid acid catalysts could efficiently convert lignin into value added aromatic monomers with 60% yields and ca. 95% mass balance when depolymerization reactions were carried out at 250 degrees C for 30-120 minutes. We found that the reaction parameters have a remarkable effect on improving the yields.

Solid base supported metal catalysts for the oxidation and hydrogenation of sugars - Tathod, Anup; Kane, Tanushree; Sanil, E. S.; Dhepe, Paresh Laxmikant (Journal of Molecular Catalysis A-Chemical, 2014)
Pt impregnated on gamma-Al2O3 (acidic support) and hydrotalcite (basic support) catalysts were synthesized, characterized and used in the oxidation and hydrogenation reactions of C5 and C6 sugars. In the absence of homogeneous base, 83% yield for gluconic acid; an oxidation product of glucose can be achieved over Pt/hydrotalcite (HT) catalyst at 50 degrees C under atmospheric oxygen pressure. Similarly, 57% yield for xylonic acid, an oxidation product of xylose is also possible over Pt/HT catalyst. Hydrogenation of glucose conducted using Pt/gamma-Al2O3 + HT catalytic system showed 68% sugar alcohols (sorbitol + mannitol) formation. The 82% yield for C5 sugar alcohols (xylitol + arabitol) was obtained by subjecting xylose to hydrogenation over Pt/gamma-Al2O3 + HT at 60 degrees C. UV analysis helped to establish the fact that under alkaline conditions sugars prefer to remain in open chain form in the solution and thus exposes -CHO group which further undergoes oxidation and hydrogenation reactions to yield acids and alcohols. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Hydrogenation; Oxidation; Solid base; Sugars; Supported metal catalysts

Synthesis of 2,5-furandicarboxylic acid by the aerobic oxidation of 5-hydroxymethyl furfural over supported metal catalysts - Sahu, Ramakanta; Dhepe, Paresh Laxmikant (Reaction Kinetics Mechanisms and Catalysis, 2014)
Supported Pt catalysts are synthesized, characterized and are used in the liquid phase air oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA). Under the optimum reaction conditions of a stepwise increase in the reaction temperature (75 and 140 degrees C for 12 h each), we achieved as high as 96 % FDCA yield in presence of 1 bar oxygen pressure over Pt/c-Al2O3. It is shown that as the oxygen pressure increases (1-10 bar), the FDCA yields decrease, since at higher partial pressure of oxygen, overoxidation reactions of substrate and product(s) are possible. It is interesting to note that even with air as an oxidant, we obtained similar yields of FDCA as that with oxygen. Moreover, the effects of base (weak or strong), its concentration (equimolar or excess) were studied in detail. It is important to increase the reaction temperature in a stepwise manner to achieve higher yields of FDCA since at higher temperatures HMF undergoes self-degradation and thus the yields of FDCA decrease. The self-degradation of HMF is also proved by undertaking the reaction under nitrogen environment. The study on the effect of substrate-to-catalyst ratio is done to improve up on the economics of overall process. The effect of supports (reducible and non-reducible) and their oxygen storage capacity is discussed and is proposed to be one of the factors to change the course of reaction. Furthermore, we have shown that FDCA formed in the reaction can be successfully isolated (91 %, isolated yield) in the pure form and its purity is confirmed by NMR, melting point, and elemental analysis. The catalysts were characterized with X-ray powder diffraction, transmission electron microscopy and inductively coupled plasma-optical emission spectroscopy techniques.
Keywords: Biomass; FDCA; green chemistry; heterogeneous catalyst; HMF; Impregnation; Oxidation

Solid acid catalyzed synthesis of furans from carbohydrates - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (Catalysis Reviews-Science and Engineering, 2016)
The alternative feedstock, biomass (particularly lignocelluloses), having the profuse availability, is promising for the synthesis of several value-added chemicals which are currently obtained from fossil feedstock. In this article, the synthesis of two extremely significant furan chemicals viz. furfural and 5-hydroxymethylfurfural (HMF) are discussed. In the synthesis of furans from biomass, numerous challenges, i.e., use of edible sugars as substrates, selectivity to furans, their isolation in pure form, reuse of catalyst, environmental issues, etc., are perceived and in the recent past researchers tried to resolve those by developing advance methodologies. This article comprehensively summarizes the latest progress made in the above-mentioned areas and also provides commentary on the analyses of results, rationale for observed activity and mechanisms, etc. It also discusses future aspects of this work.
Keywords: Biomass conversion; carbohydrates; cellulose; furans; furfural; hemicelluloses; HMF; solid acid catalyst

Solid base catalyzed depolymerization of lignin into low molecular weight products - Chaudhary, Richa; Dhepe, Paresh Laxmikant (Green Chemistry, 2017)
For the biorefinery concept to become commercially viable, it is essential to add value to lignin which is the only naturally available aromatic polymer. A one-pot depolymerization of lignin into reactive substituted phenolic compounds (platform chemicals and octane enhancers) with low molecular weight is of paramount importance and for that, the development of an environmentally benign method is necessary. Herein we report the depolymerization of high molecular weight lignin (60 000 Da) over various recyclable solid base catalysts at 250 degrees C over 1 h. Under these conditions, most of the zeolitic catalysts (NaX, NaY, NaP) showed very high yields of low molecular weight products compared to other catalysts (MgO, CaO, HT, HAP). But in particular, over NaX the maximum yield (51%) of low molecular weight products was achieved. Identification and quantification of products was done by GC, GC-MS, HPLC, LC-MS, CHNS, NMR and FT-IR techniques. The revelation of retention of most of the functional groups on products present in lignin was confirmed by FT-IR studies. It is observed that the efficiencies of catalysts were dependent on pH, the cation, the type and concentration of basic sites, etc. A unique study on the product adsorption capacities on solids was done and it is recognized that as the strength of basic sites increases, adsorption enhances.